1991
DOI: 10.1111/j.1365-2230.1991.tb01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis herpetiformis associated with ulcerative colitis

Abstract: Over the past 20-years, it has been shown that the majority of patients with dermatitis herpetiformis (D.H.) suffer from coeliac disease of varying intensity. Dermatitis herpetiformis may also be associated with other autoimmune diseases but only exceptionally with chronic ulcerative colitis (U.C.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…Sulfasalazine is a readily available and well‐tolerated medication, effective in the long‐term management of inflammatory bowel disease and rheumatoid arthritis. There have been three previous reports of its successful use in DH 1–3 . These cases indicate that sulfasalazine might be as effective as the sulphone, dapsone, in controlling this condition in some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfasalazine is a readily available and well‐tolerated medication, effective in the long‐term management of inflammatory bowel disease and rheumatoid arthritis. There have been three previous reports of its successful use in DH 1–3 . These cases indicate that sulfasalazine might be as effective as the sulphone, dapsone, in controlling this condition in some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been eight reported cases of ulcerative colitis associated with dermatitis herpetiformis (Table 1) (7,12,(23)(24)(25)(26)(27). Davies et al (12) reported 2 such cases of 42 patients, and Yasui et al (7) reported 1 such case of 49 Japanese patients with dermatitis herpetiformis.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al (12) reported 2 such cases of 42 patients, and Yasui et al (7) reported 1 such case of 49 Japanese patients with dermatitis herpetiformis. Ulcerative colitis preceded dermatitis herpetiformis in the seven cases for which the temporal sequence was described (7,12,23,(25)(26)(27). As for the pattern of IgA deposits, three were granular (1 2, 26,27), the Japanese case was linear (7), and data were not available for the remaining four cases (12,23,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations